2007
DOI: 10.1111/j.1365-2222.2007.02861.x
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the association between high levels of immunoglobulin E food sensitization and eczema in infancy: an international study

Abstract: Early-onset severe eczema in infancy was associated with HR-IgE-FS. Clinical implications Food allergies should be routinely assessed in infants with moderate or severe eczema. Capsule summary In eczematous infants, the earlier the age of onset, and the greater the severity of eczema, the greater the frequency of associated high levels of IgE-FS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 37 publications
(66 reference statements)
4
132
2
8
Order By: Relevance
“…En otro estudio, 82% de 138 enfermos con alergia al maní tenían DA 31 . Finalmente en el tercer estudio, los enfermos que presentaban DA severa en los primeros 3 meses de vida tenían con mayor frecuencia IgE específica a leche de vaca, huevo y maní sugiriendo que este grupo tiene mayor riesgo de manifestar AA mediada por IgE 32 . Estos estudios sugieren fuertemente que AA y DA moderada a severa se presentan con frecuencia en un mismo niño y que la DA severa de comienzo precoz se asocia con riesgo alto de sensibilización a alimentos.…”
Section: Estudios De Laboratoriounclassified
“…En otro estudio, 82% de 138 enfermos con alergia al maní tenían DA 31 . Finalmente en el tercer estudio, los enfermos que presentaban DA severa en los primeros 3 meses de vida tenían con mayor frecuencia IgE específica a leche de vaca, huevo y maní sugiriendo que este grupo tiene mayor riesgo de manifestar AA mediada por IgE 32 . Estos estudios sugieren fuertemente que AA y DA moderada a severa se presentan con frecuencia en un mismo niño y que la DA severa de comienzo precoz se asocia con riesgo alto de sensibilización a alimentos.…”
Section: Estudios De Laboratoriounclassified
“…6 Egg sensitization is closely associated with AD, the level of which is apparently correlated with the severity of this disease. 7,8 In 2001, we initiated a population-based cohort study on nursery school children aged 6 years and under, on Ishigaki Island, Okinawa, Japan, which was named the Kyushu University Ishigaki Atopic Dermatitis Study (KIDS). Through this cohort study, we have reported AD prevalence, serum total IgE and chemokine (C-C motif) ligand (CCL)17/thymus and activation regulated chemokine (TARC) levels, spontaneous regression ratio, risk factors for AD, and the relationship between skin infections and childhood AD.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that allergic sensitization to food antigens may occur before oral ingestion, such as through inflamed skin (35)(36)(37). Current theories suggest that allergic sensitization occurs through skin exposure and early oral consumption of commonly allergic foods will induce oral tolerance, thereby inhibiting the development of allergy (38,39). This is supported by lower rates of certain food allergies in countries where children have early oral exposure (40) and several published studies (14)(15)(16)(17)(18) have concluded that delayed introduction of commonly allergenic foods does not prevent allergic disease.…”
Section: Discussionmentioning
confidence: 99%